1998
DOI: 10.3354/meps172127
|View full text |Cite
|
Sign up to set email alerts
|

A high frequency time series at weathership M, Norwegian Sea, during the 1997 spring bloom: feeding of adult female Calanus finmarchicus

Abstract: The feeding ecology of Calanus finmarchicus was investigated during spring 1997 at a permanent station in the Norwegian Sea (Stn M, 66"N, 2"E) as part of the TASC (Trans Atlantic Study of Calanus finmarchicus) project time-series investigations. The phytoplankton bloom began in mid May, coinciding m t h the onset of the stratification, and was mainly composed of d~atoms and prymnesiophytes. Daily Ingestion of phytoplankton by C. finmarchicus was about 2% of body carbon for the long period before the bloom, 30%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
63
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 36 publications
12
63
2
Order By: Relevance
“…4) is very similar to the one measured during the spring bloom in May 1997 at Weathership M (i.e. 80 to 130 chl a mg m -2 ) (Irigoien et al 1998). …”
Section: Winter Versus Spring Biomasssupporting
confidence: 68%
See 1 more Smart Citation
“…4) is very similar to the one measured during the spring bloom in May 1997 at Weathership M (i.e. 80 to 130 chl a mg m -2 ) (Irigoien et al 1998). …”
Section: Winter Versus Spring Biomasssupporting
confidence: 68%
“…An inspection of data obtained in early 1997 at Weathership M (Irigoien et al 1998, Dale et al 1999) revealed interesting features in time series of phytoplankton measured near the sea surface and at a depth of 100 m (Fig. 7), respectively.…”
Section: Transition From CML To Seasonal Thermoclinementioning
confidence: 94%
“…Although EP rates for C. finmarchicus were reduced during 2000, they were not reduced as greatly as may have been expected given the very low food levels (total chl a < 0.5 µg l -1 , > 5 µm chl a essentially zero), and our observations on GB during a post-spring bloom period when EP ceased while total chl a was around 0.5 µg l -1 (Campbell et al 2001a). A conclusion might be that EP by females, just after they emerge from diapause in winter and early spring, depends more on internal sources of energy than on external sources (Irigoien et al 1998). However, there is conflicting evidence on this issue at present.…”
Section: Discussionsupporting
confidence: 52%
“…In contrast, significant rates of EP by C. finmarchicus have been observed at pre-bloom chl a concentrations of only 0.2 to 0.4 µg l -1 (Niehoff et al 1999, Richardson et al 1999, this study). In 2 of these studies, measured (Irigoien et al 1998) and estimated (Richardson et al 1999) ingestion rates were insufficient to cover the energetic costs of EP. It is possible that in this species of Calanus, internal lipid stores provide most of the energetic requirements and some level of ingested material is required for gonad maturation and subsequent egg production (Ohman & Runge 1994, Niehoff et al 1999.…”
Section: Discussionmentioning
confidence: 99%
“…nauplii on ciliates and diatoms, and avoiding the Phaeocystis sp. is possible (Irigoien et al 1998(Irigoien et al , 2000. In this situation, the mesozooplankton is actually removing the predators of small flagellates and picoplankton and diatoms, the possible competitors of Phaeocystis sp.…”
Section: Vertical Chlorophyll a Distributionmentioning
confidence: 99%